Pharmacokinetics and tissue distribution of Ramulus Mori (Sangzhi) alkaloids in rats and its effects on liver enzyme activity - Liu, Zhihua; Feng, Yu; Zhao, Hang; Hu, Jinping; Chen, Yanmin; Liu, Dongdong; Wang, Hongliang; Zhu, Xiangyang; Yang, Hongzhen; Shen, Zhufang; Xia, Xuejun; Ye, Jun; et al. (Frontiers in Pharmacology, 2023)
Ramulus Mori (Sangzhi) alkaloids (SZ-A) derived from twigs of mulberry (Morus alba L., genus Morus in the Moraceae family) was approved by the National Medical Products Administration in 2020 for the treatment of type 2 diabetes mellitus. In addition to excellent hypoglycemic effect, increasing evidence has confirmed that SZ-A exerts multiple pharmacological effects, such as protecting pancreatic β-cell function, stimulating adiponectin expression, and alleviating hepatic steatosis. Importantly, a specific distribution of SZ-A in target tissues following oral absorption into the blood is essential for the induction of multiple pharmacological effects. However, there is a lack of studies thoroughly exploring the pharmacokinetic profiles and tissue distribution of SZ-A following oral absorption into the blood, particularly dose-linear pharmacokinetics and target tissue distribution associated with glycolipid metabolic diseases. In the present study, we systematically investigated the pharmacokinetics and tissue distribution of SZ-A and its metabolites in human and rat liver microsomes, and rat plasma, as well as its effects on the activity of hepatic cytochrome P450 enzymes (CYP450s). The results revealed that SZ-A was rapidly absorbed into the blood, exhibited linear pharmacokinetic characteristics in the dose range of 25–200 mg/kg, and was broadly distributed in glycolipid metabolism-related tissues. The highest SZ-A concentrations were observed in the kidney, liver, and aortic vessels, followed by the brown and subcutaneous adipose tissues, and the heart, spleen, lung, muscle, pancreas, and brain. Except for the trace oxidation products produced by fagomine, other phase I or phase II metabolites were not detected. SZ-A had no inhibitory or activating effects on major CYP450s. Conclusively, SZ-A is rapidly and widely distributed in target tissues, with good metabolic stability and a low risk of triggering drug-drug interactions. This study provides a framework for deciphering the material basis of the multiple pharmacological functions of SZ-A, its rational clinical use, and the expansion of its indications.